1999
DOI: 10.1292/jvms.61.27
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Analysis of c-yes and c-erbB-2 Oncogene Products and p53 Tumor Suppressor Protein in Canine Mammary Tumors

Abstract: In order to evaluate the involvement of c-yes and c-erbB-2 oncogene products, and p53 tumor suppressor protein in canine mammary neoplastic lesions, sections of archived paraffin-embedded samples of 79 mammary tumors were analyzed immunohistochemically using antibodies against human c-yes p62 and c-erbB-2 products and p53. These 79 tumors were divided into 2 groups: 32 benign (2 adenosis, 7 simple adenomas, 14 complex adenomas, and 9 benign mixed mammary tumors) and 47 malignant tumors (26 simple adenocarcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
3
11

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 24 publications
4
54
3
11
Order By: Relevance
“…The p53 mutation used as a risk factor for increased risk of recurrence and death from breast cancer independent of tumour size, hormone receptor levels (Iacopetta et al, 1998). The results of the present study are in agreement with other researcher (Rungzipipat et al, 1999), who also observed p53 overexpression in different canine tumours. Determination of the p53 status in canine cancer patients helped in investigating the role of p53 in mammary tumour formation and its progression (Veldhoen et al, 1999).…”
Section: Discussionsupporting
confidence: 94%
“…The p53 mutation used as a risk factor for increased risk of recurrence and death from breast cancer independent of tumour size, hormone receptor levels (Iacopetta et al, 1998). The results of the present study are in agreement with other researcher (Rungzipipat et al, 1999), who also observed p53 overexpression in different canine tumours. Determination of the p53 status in canine cancer patients helped in investigating the role of p53 in mammary tumour formation and its progression (Veldhoen et al, 1999).…”
Section: Discussionsupporting
confidence: 94%
“…In our study, the highest expression of p53 was observed in complex carcinomas and in 1 st and 2 nd grade malignant tumors. These results are consistent with the results obtained by Rungsipipata (1999), who found the highest levels of p53 expression in simple and complex carcinomas and also showed expression of this protein in adenomas (16%) (Rungspipata, 1999). Rodo (2007) obtained results on the expression of p53 , stating that there is a positive correlation between proliferative activity and the number of cells expressing p53 protein (Rodo, 2007).…”
Section: Discusionsupporting
confidence: 92%
“…In the present case the tumours T-2 and T-3 were positive for c-erbB2 overexpression while T-1 was negative. Both T-2 and T-3 consisted of neoplastic cells of epithelial origin and it has been reported that c-erbB2 overexpression is mostly restricted to mammary tumours of epithelial origin (Yakota et al, 1986;Rungsipipat et al, 1999;Kumar et al, 2009). Overexpression of c-erbB2 has been correlated with poor prognosis of human breast cancers by many researchers (Yakota et al, 1986;Bruman et al, 1990).…”
Section: Discussionmentioning
confidence: 99%